The Correlation between self-efficacy and iron tablets consuming of Pregnant Women in Garut District - Puspita, Tantri; Jerayingmongkol, Peranan; Sanguanprasit, Boosaba (Universitas Negeri Semarang in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2019)
Maternal health during pregnancy is important not only for the mothers but also for the infant. Anemia status is a condition that may cause a death against pregnant women. Consuming iron tablet lead pregnant women to prevent anemia. The purpose of this study was to identify the relationship between self-efficacy and consuming iron tablet during pregnancy. This study was a secondary analysis from previous study which included 263 pregnant women in the analysis. The pregnant women were in 5 Public Health Care area in Garut District. The Data were collected using self-administered questionnaire. The result revealed that more than 50 %  participant were confident and highly confident of taking iron tablets. Amount 22% of them were always consumed the iron tablet as they daily supplement. There was moderate correlation between self-efficacy and iron tablet consuming of pregnancy women in Garut District (r =407, α< 0,01). Health care providers are recommended to enhance pregnant women iron tablet consuming by improve their self-efficacy. It also can include their family as their motivator of improving self-efficacy to consume iron tablets.